The Legal Politics of Restorative Justice in Indonesia - Ahmad Nur Rohadi; Nanik Prasetyoningsih (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Restorative Justice needs to be implemented immediately in Indonesia. Law Number 1 of 2023, which is expected to be an oasis, does not regulate this matter optimally. This article will discuss the ideal form of regulation for implementing restorative Justice in Indonesia. Implementing restorative Justice will include more than procedural or formal law. More than that, restorative Justice must cover all aspects of criminal law enforcement. It starts from material criminal law, procedural law, litigation dispute resolution, and non-litigation case resolution. This article will use normative juridical research methods and conceptual and statutory approaches. One of the important findings in this article is the absolute need for a paradigm shift in the enforcement and regulation of criminal law. From the initial nuance of retribution to a more nuanced recovery approach (restorative). Then therapeutic justice regulation must also be included in material criminal law regulation. So, it can be used as a guide for law enforcement officials in finding substantive Justice.